(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The crisis currently affecting the firms, joined to the technological development and more intense global competition have transformed the current competitive environment for most firms. Firms competitive advantage is now more dependent on continuous knowledge development and enhancement, so knowledge becomes a central theme in strategic management. Furthermore, the competitiveness of a company and the health of the communities around it are closely intertwined. The business needs a successful community, both to create demand for its products and to provide critical assets and a supportive environment and, also, community needs successful businesses to provide wealth creation opportunities. This scenario calls for a broader definition of business success which includes customer engagement methods and shifts the central goal of companies into creating shared value. This aim becomes more influential especially for those companies who operate in a new market space through electronic means that enable electronic marketing relationships from the perspective of non-conventional marketing and social-media marketing. Social Media (SM) and ICT enable the interactionwith the market that allows spreading development burden amongst companies and individuals. Firms increasingly have needs of gathering ideas for innovations and providing solutions to existing problems and/or for maintaining the competitive advantage. More and more companies apply the wisdom of crowds to certain tasks and challenges, making the crowdsourcing a recognized mechanism for problem-solving. While both phenomena are not new, their overlapping requires considerable attention in practice, related to the crowdsourcing opportunities and benefits that have been enabled by new web 2.0 technologies. Crowdsourcing presents a number of potential applications, open to future developments and seem to provide new channels and ways to enable this in practice and to create new shared value and firm value. Based on theoretical conceptualization, combined with empirical evidence, we develop an analysis framework for approaching crowdsourcing in a SME context. In particular, we aim to highlight the influence of customer-social engagement through new technologies on shared value creation and stress the role of crowdsourcing process in knowledge-building process. Finally, authors analyze if those instances are able to contribute to build and develop the firms performance.